School Burnout, Relational, and Organizational Factors - Parrello, Santa; Ambrosetti, Alice; Iorio, Ilaria; Castelli, Luciana (Frontiers in Psychology, 2019)
Work stress and burnout affect teachers to a significant extent (Kyriacou, 2011). The objective of this study is to evaluate and compare the impact of relational and organizational factors on teacher burnout in two samples of primary school teachers, one Italian (Naples) and one Swiss (Cantone Ticino). The hypothesis is that, given the socio-cultural and economic differences of the two contexts, the variables under investigation impact teacher burnout differently. We collected data through a self-reported questionnaire containing the following scales: Copenhagen Burnout Inventory, Satisfaction with Life Scale, Life Orientation test, Organizational identification, Colleague support, Workload. The Swiss sample consists of 964 teachers (26% kindergarten, 73.7% primary school teachers); the Italian sample consists of 104 teachers (20% kindergarten, 80% primary schools teachers). Descriptive analyses, mean comparison (t-test), correlational analyses and multiple linear regression analyses were conducted. There are no significant differences between the two samples with respect to burnout, colleague support and workload. Correlations between burnout and the variables under investigation are significant in both samples, except for optimism in the Italian sample. Regression analysis shows that optimism and colleague support have an impact on burnout only in the Swiss sample; organizational identification has a stronger impact on burnout in the Italian sample.